Changes in warehouse spatial patterns and rental prices: Are they related? Exploring the case of US metropolitan areas. (October 2022) - Oliveira, Renata Lúcia Magalhães de; Dablanc, Laetitia; Schorung, Matthieu
Abstract: In this paper, two hypotheses are explored linking urban characteristics to the spatial structure of warehouses: (i) the location of warehouses (central places or peripheral areas) is closely related to the land/rent values of these facilities; and (ii) logistics sprawl is higher in cities with a high differential between land/rent values in city centers and peripheral areas. For that, we have considered warehouse real estate and urban data for 46 United States metropolitan areas to analyze the urban spatial structure and the relationship among urban variables, warehouse location, and rental prices. We deliver an exploratory analysis among the 46 metropolitan areas. The main results are (i) it is essential to classify metropolitan portions of urban space into a typology to perform studies that consider different regions; (ii) warehouse location and rent prices are related to the concentration of urban activity; (iii) logistics sprawl is not significantly related to differential warehouse rental prices in the database that we explored. Highlights: We examine relationships between the logistics real estate market and warehouse spatial patterns in US metropolitan areas. We propose a typology of sub-areas within metropolitan areas based on the density of activities, namely Urban Activity Index. We observe that average warehouse rental prices statistically depend on the location of warehouses. The relationship between the differential warehouse prices and the yearly logistics sprawl is not statistically significant.